Biological control of the cassava mealybug, Phenacoccus manihoti (Hom., Pseudococcidae), by Epidinocarsis lopezi (Hym., Encyrtidae) in Malawi - Neuenschwander, Peter; Borowka, R.; Phiri, G.; Hammans, H.; Nyirenda, S.; Kapeya, E.H.; Gadabu, A. (Informa UK Limited, 1991)
From 1985 to 1989 five large scale surveys were made to document the spread of the cassava mealybug (CM) Phenacoccus manihoti Matile‐Ferrero (Hom., Pseudococcidae) and the releases and successful establishment of its exotic parasitoid Epidinocarsis lopezi (De Santis) (Hym., Encyrtidae) through most cassava‐growing areas of Malawi. In a multiple regression analysis involving 29 meteorological, agronomic and plant variables from 476 fields, the duration of E. lopezi's presence was the major factor influencing CM population densities. In the first year the CM was recorded in a particular place, 25% of all tips had more than 100 CM. Wherever E. lopezi had been present for two years or more, CM populations were reduced on average seven times and tips infested with more than 100 CM became rare (1%). In parallel, damage on cassava tips stabilized at a low level. Similarly, along Lake Malawi, 84.9% of all tips had more than 10 CM in 1986; this value stabilized at 3.3%‐4.0% in 1988–1989. Indigenous coccinellids were often abundant in the first year of the CM infestation, but their populations collapsed later, while the frequency of fields with E. lopezi increased. In 1987, farmers abandoned 28.4% of all fields where E. lopezi was just introduced as compared with 2.7% where the parasitoid had been present for two years or more. Overall, satisfactory control was achieved by E. lopezi in all but a few fields concentrated on extremely poor soils characterized by sand dune vegetation. The socioeconomic implications of this ongoing and apparently successful biological control program are discussed.